2008
DOI: 10.3311/pp.ch.2008-2.01
|View full text |Cite
|
Sign up to set email alerts
|

An alternative procedure for modeling of Knudsen flow and surface diffusion

Abstract: An alternative procedure for the calculation of impingement rate distribution and simultaneously the transmission probability in pores under Knudsen diffusion conditions is introduced. It is based on a combination of the finite difference method and a projection approach. Pore entrance and exit effects, and the influence of the pore length on diffusive fluxes are investigated. Later on, it is applied for a simultaneous Knudsen and surface flow system. In the model, the equation system is built without the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…well [256,[471][472][473]. Hesse [473] has demonstrated that pore lengths close to the average pore diameters lead to a higher transport resistance than obtained from the usual models, in agreement with Eq.…”
Section: Knudsen Diffusion In Pore Channelssupporting
confidence: 70%
See 3 more Smart Citations
“…well [256,[471][472][473]. Hesse [473] has demonstrated that pore lengths close to the average pore diameters lead to a higher transport resistance than obtained from the usual models, in agreement with Eq.…”
Section: Knudsen Diffusion In Pore Channelssupporting
confidence: 70%
“…For gases, a unique nano-confinement phenomenon occurs that has been studied since the beginning of the 20th Century, and is called Knudsen diffusion [3,[256][257][258][259][260][261][262][263][264][265][266][267][268][269][270][271][272], after Martin Knudsen [273,274], who first described it as "molecular flow" (German: Molekularströmung). When the mean free path of gas molecules, , becomes larger or is of the same order of magnitude as the local channel diameter, d , the frequency of the collisions between the molecules and the walls exceeds the intermolecular collision frequency.…”
Section: General Features Of Diffusion In Mesoporous Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…20) Knudsen transport and surface diffusion can be viewed as separate, independent fluxes or as synergistic, interdependent modes of neutral transport. 20,21) Another benefit of the leaner chemistry used in lowtemperature etching is an improved mask morphology, which translates into improved circularity and sidewall roughness of the etched holes, as shown in Fig. 4.…”
Section: Har Etch Mechanismsmentioning
confidence: 99%